Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Reaction between lawsone and aminophenol derivatives: synthesis, characterization, molecular structures and antiproliferative activity - Kathawate, Laxmi; Joshi, Pranya V.; Dash, Tapan Kumar; Pal, Sanjima; Nikalje, Milind; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Reaction between two bioreductive reactants lawsone (2-hydroxy-1,4-napthoquinone) and derivatives 2-aminophenol without catalyst is reported. The reaction between lawsone and 4-chloro-2-aminophenol leads to formation of red colored major product 1A:[2-[(5-chloro-hydroxyphenyl)amino]naphthalene-1,4-dione] and fluorescent orange colored minor compound 1B:[10-chloro-benzo[alpha]phenoxazine-5-one]. Molecular structure of 1A and 1B were determined by single crystal X-ray diffraction. Two mechanisms were proposed to the formation of red 1A and 1B. `Ortho-para' tautomeric equilibrium was observed in DMSO-d(6) solution in 1A, which was revealed by H-1, C-13 NMR and LC-MS studies. Molecules of 1A formed dimers via N-H center dot center dot center dot O interaction and polymeric chain of dimers was formed by OH center dot center dot center dot O interactions. Cl center dot center dot center dot Cl interactions were observed between the polymeric chains of dimers in 1A. Molecules of 1B show Cl center dot center dot center dot N interaction. Antiproliferative properties is studied for 1A-5A compounds (obtained by the reaction of lawsone with 2-amino-4-methylpheno1;2A, 2-aminopheno1;3A, 3-aminophenol;4A and 4-aminophenol;5A) and evaluated against two cancer cell lines, THP1 (human monocytic leukemia cells) and COLO205 (colorectal adenocarcinoma) and one normal cell line, HEK293T (human embryonic kidney). The values of 50% inhibitory concentration (IC50) of compounds 1A-5A was determined using XTT assay. The cytotoxic effects of compounds 2A and 3A were observed against COLO205 and compounds 4A and 5A on THP1 were observed to be higher in comparison to their effect on HEK293T cell lines. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Aminophenol; Benzo[alpha]phenoxazine; Cl center dot center dot center dot N interactions; Lawsone; pi-pi stacking interaction

Synthesis, characterization and molecular structures of homologated analogs of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone - Salunke-Gawali, Sunita; Pawar, Omkar; Nikalje, Milind; Patil, Rishikesh; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath (Journal of Molecular Structure, 2014)
Four analogues of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone (where n-alkyl is methyl in L-1Br, ethyl in L-2Br, propyl in L-3Br and butyl in L-4Br) are synthesized and characterized. A reaction mechanism is proposed for the formation of L-1 Br to L-4Br from the starting material 2,3-dibromo-1,4-naphthoquinone. The v(N-H) frequency in the FT-IR spectra is affected by the intramolecular hydrogen bonding in L-1Br to L-4Br and is observed similar to 3267 cm(-1) in L-2Br. A shift of similar to 25 cm(-1) is observed in the v(C-Br) frequency in all the compounds as compared to 2,3-dibromo-1,4-naphthoquinone (627 cm(-1)). A broad charge transfer band is observed between 400 and 600 nm in the UV-Vis spectra, which imparts red colour to all the compounds. Molecular structures of L-2Br and L-3Br were studied by single crystal X-ray diffraction studies. Molecules of L-2Br crystallize in Pca2(1), whereas the molecule L-3Br crystallizes in the P-1 space group. Molecules of L-2Br forms a polymeric chain through N-H...O interaction and forms beautiful butterfly like arrangement of molecules when viewed down the `a' axis. Ladder like polymeric chain of molecules is observed in L-3Br via C-H...O and N-H...O interactions. Every alternating neighbouring chains of L-3Br, show pi-pi stacking interactions between the quinonoid rings of the molecules, however this interaction is not observed in L-2Br. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Dibromo-1; 4-naphthoquinone; Aminonaphthoquinone; hydrogen bonding; Michael addition; pi-pi stacking

Targeting a chemorefractory COLO205 (BRAF V600E) cell line using substituted benzo[alpha]phenoxazines - Pal, Sanjima; Konkimalla, V. Badireenath; Kathawate, Laxmi; Rao, Soniya S.; Gejji, Shridhar P.; Puranik, Vedavati G.; Weyhermueller, Thomas; Salunke-Gawali, Sunita (RSC Advances, 2015)
Mutational activations of the oncogene BRAF (especially BRAF V600E) result in a poor prognosis for colon cancer patients and are associated with chemoresistance rendering them refractory to treatment. The development of novel bioactive compounds with specific targeting abilities under such conditions is an urgent need in drug discovery. In this report we synthesize and characterize three fluorescent benzo[alpha]phenoxazine compounds (10R-benzo[alpha]phenoxazine-5-one, 1B; R = Cl, 2B; R = CH3, 3B; R = H) and their anticancer activities are evaluated in a COLO205 cell line. All three compounds with a log P value around 2 were cell permeable. However, 2B and 3B showed specific cytotoxicity in a malignant COLO205 cell line with a BRAF mutation (V600E) in comparison to a non-malignant wild-type BRAF HEK293T cell line. From further cell-based assays (cell cycle analysis, DNA fragmentation and caspase activation), we conclude that 2B and 3B treatment-induced selective cell death by inducing cell cycle arrest at the G0/G1 phase and caspase-mediated apoptosis (activation of the intrinsic and extrinsic pathways) are present only in BRAF V600E COLO205 cells. Further studies in the drug discovery pipeline might help develop these benzo[alpha]phenoxazines as promising chemotherapeutics for such refractory mutated cancers.

Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes